Tuning of TiO2 Photocatalytic Efficiency: Insights into Hydrothermal and Sol-Gel Synthesised Undoped and Rare Earth-Doped Nanoparticles - Sunanda; Narwal, Pooja; Singh, Pamela; Dehiya, Brijnandan S. (Asian Journal of Chemistry, 2026)
This study investigates the synthesis, characterisation and photocatalytic performance of TiO2 nanoparticles without doping and after doping with samarium and neodymium. Two synthesis methods, hydrothermal and sol-gel were employed, using titanium tetraisopropoxide (TTIP) as precursor. The TiO2 nanoparticles obtained were in anatase form using the TTIP precursor. The characterisation techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR) and UV-Vis spectroscopy, provided insight into particle size, morphology, crystalline structure and photocatalytic properties. The photocatalytic efficacy was assessed by methylene blue degradation under visible light irradiation. The study reveals distinct doping effects, where Sm and Nd shift TiO2 absorption edge to the UV region. SEM analysis showed uniform particle distribution with varied morphology depending on synthesis method and the dopants added. XRD data confirmed lattice incorporation of dopants without phase separation. FTIR spectra showed functional groups consistent with rare earth metal-doped TiO2. Particle sizes, calculated by Scherrer’s equation, were generally under 50 nm, with sol-gel and hydrothermal methods affecting crystallinity and agglomeration. This research also underscores the effects of doping for altering the photocatalytic mechanisms and opens avenues for further study into TiO2-based photocatalysts in environmental and industrial applications.